Smart Administration– Really? Why Not? Introduction - Korczak, Jerzy (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
In an increasingly smarter world, where increasingly more areas of social life are encompassed by “smart solutions”, public administration cannot remain on the outside or in opposition to this process. The scholars of the Section of the Public Administration System at the Institute of Administrative Sciences of Faculty of Law, Administration and Economics at the University of Wrocław, have decided to devote a collective publication to the matter of smart administration. The articles comprising this volume present a rich array of topics related to the issue of smart administration, as each of the authors has chosen a different area of administrative activity.
Keywords: administracja publiczna; inteligentna organizacja